1987
DOI: 10.1002/1098-108x(198707)6:4<537::aid-eat2260060410>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Hyperamylasemia and bulimia: A clinical review

Abstract: Hyperamylasemia, often with abdominal symptoms, commonly occurs in patients with bulimia as well as in pancreatitis. Eleven bulimic patients presenting with hyperamylasemia are described; one case is described in detail. Of the 11, the source of amylase in 10 was salivary, not pancreatic. A careful history with questions about weight changes, eating behavior, body image, methods of weight control and purging, as well as a complete mental status examination should be done on females presenting with the above sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…The S3 fraction was not found in 3 of 13 patients with bulimia or in 2 of the 16 patients with bulimia. These findings are in agreement with another report (Kaplan, 1987) that found 10 of 11 bulimics to have elevated salivary isoenzymes. Only 2 of the 16 restrictor anorectics demonstrated modestly elevated serum lipase activity; both patients also showed pathologically but modestly elevated P-amylase activity in serum.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The S3 fraction was not found in 3 of 13 patients with bulimia or in 2 of the 16 patients with bulimia. These findings are in agreement with another report (Kaplan, 1987) that found 10 of 11 bulimics to have elevated salivary isoenzymes. Only 2 of the 16 restrictor anorectics demonstrated modestly elevated serum lipase activity; both patients also showed pathologically but modestly elevated P-amylase activity in serum.…”
Section: Resultssupporting
confidence: 93%
“…No significant difference in serum lipase activity (p = .32) was found between the two groups. Other researchers (Kaplan, 1987;Humphries et al, 1987) also demonstrated that pancreas involvement in hyperamylasemia in patients with eating disorders can be largely ruled out. Of the patients with bulimia nervosa, 20% can be termed ruminants (Levine, Wingate, & Pfeffer, 1983;Fairburn & Cooper, 1984;Blinder, 1986;Larocca & Della-Fera, 1987).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical complications of bulimia nervosa have been well described. These complications are multisystemic and include abnormalities in the head and neck (Kaplan, 1987;Pyle, Mitchell and Eckert, 1981). For the most part, these have been primarily dental (caries, gingivities, and demineraliza tion with loss of tooth substance), but bilateral parotid gland enlargement has also been identified.…”
mentioning
confidence: 99%
“…For the most part, these have been primarily dental (caries, gingivities, and demineraliza tion with loss of tooth substance), but bilateral parotid gland enlargement has also been identified. Parotid involvement, although relatively uncommon, is usually painless and often accompanied by salivary hyperamylasemia (Kaplan, 1987).…”
mentioning
confidence: 99%